2012
DOI: 10.1002/bies.201100130
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signalling: Its unpopular beginning, its acceptance and its exciting future

Abstract: Adenosine 5'-triphosphate (ATP) was identified in 1970 as the transmitter responsible for non-adrenergic, non-cholinergic neurotransmission in the gut and bladder and the term 'purinergic' was coined. Purinergic cotransmission was proposed in 1976 and ATP is now recognized as a cotransmitter in all nerves in the peripheral and central nervous systems. P1 (adenosine) and P2 (ATP) receptors were distinguished in 1978. Cloning of these receptors in the early 1990s was a turning point in the acceptance of the puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
189
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(200 citation statements)
references
References 111 publications
(112 reference statements)
2
189
1
8
Order By: Relevance
“…3 Immunostaining for P2X 1 (a, e), P2X 2 (b, f), P2X 3 (c, g) and P2X 7 to enable it to function in its roles within the suspensory apparatus of the distal phalanx in equids [22]. Previous studies in human and rat skin keratinocytes have reported the presence of P2X 2 , P2X 3 , P2X 5 and P2X 7 receptor subunits [23,24]. P2X receptors found in the skin are suggested to have an important physiological role as an initial sensor for external stimuli, and P2X 7 receptors, known to be involved in ATP-induced apoptosis, are likely to participate in the process of the end-stage terminal differentiation of keratinocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…3 Immunostaining for P2X 1 (a, e), P2X 2 (b, f), P2X 3 (c, g) and P2X 7 to enable it to function in its roles within the suspensory apparatus of the distal phalanx in equids [22]. Previous studies in human and rat skin keratinocytes have reported the presence of P2X 2 , P2X 3 , P2X 5 and P2X 7 receptor subunits [23,24]. P2X receptors found in the skin are suggested to have an important physiological role as an initial sensor for external stimuli, and P2X 7 receptors, known to be involved in ATP-induced apoptosis, are likely to participate in the process of the end-stage terminal differentiation of keratinocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmission, secretion, transduction, cell proliferation, motility, and differentiation are typical examples of biological functions modulated by nucleotides or nucleosides acting as extracellular signaling molecules [5][6][7][8][9][10][11]. Burnstock's early hypothesis that ATP, the major intracellular molecule providing the energy required for multiple biochemical and biophysical processes, may actually function as an extracellular non-adrenergic and noncholinergic signaling molecule [12,13] was received with great skepticism [14,15]. After several decades of extensive work, the scientific community came to the realization that ATP is widely employed as a signaling molecule in multiple biological processes in both normal and pathophysiological conditions [9,11,[16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…P2X and P2Y activation stimulates various downstream signalling pathways that affect many cellular processes. Although these pathways remain to be fully elucidated, it is widely accepted that purinergic signalling is involved in physiological and pathophysiological responses including neurotransmission, coagulation, inflammation, tissue regeneration, and cell proliferation, differentiation and death [7].…”
Section: Introductionmentioning
confidence: 99%